The Professional Conscience: A Psychoanalytic Study of Moral Character in Tolstoy's The Death of Ivan Ilych - Feldman, Steven P. (Journal of business ethics, 2004)
Modern professional behavior all too often fails to meet high standards of moral conduct. An important reason for this unfortunate state of affairs is the expansive self interest of the individual professional. The individual's natural desire for his/her own success and pleasure goes unchecked by internal moral constraints. In this essay, I investigate this phenomenon using the psychoanalytic concepts of the ego ideal and superego. These concepts are used to explore the internal psychological dynamics that contribute to moral decision-making. The contrasts between self interest and concern for others, selfishness and moral values, and moral conscience and social conformity are examined in Tolstoy's study of the modern professional in The Death of Ivan Ilych. By reviewing Freud's work on the moral conscience, particularly its complex inner structure and liabilities to dysfunction, and applying it to Tolstoy's penetrating portrayal of Ivan Ilych's personal and professional life, an understanding of the inner (emotional) foundation of moral character, its dependence on the past through the links between generations, and the need to integrate idealism with moral values is generated. Examples from Enron Corporation will be used throughout the paper to relate the analysis and discussion to contemporary business ethics problems.